Peroxisomes contribute to reactive oxygen species homeostasis and cell division induction in Arabidopsis protoplasts - Tiew, Terence W.-Y.; Sheahan, Michael B.; Rose, Ray J. (Frontiers in Plant Science, 2015)
The ability to induce Arabidopsis protoplasts to de-differentiate and divide provides a convenient system to analyse organelle dynamics in plant cells acquiring totipotency. Using peroxisome-targeted fluorescent proteins, we show that during protoplast culture, peroxisomes undergo massive proliferation and disperse uniformly around the cell before cell division. Peroxisome dispersion is influenced by the cytoskeleton, ensuring unbiased segregation during cell division. Considering their role in oxidative metabolism, we also investigated how peroxisomes influence homeostasis of reactive oxygen species (ROS). Protoplast isolation induces an oxidative burst, with mitochondria the likely major ROS producers. Subsequently ROS levels in protoplast cultures decline, correlating with the increase in peroxisomes, suggesting that peroxisome proliferation may also aid restoration of ROS homeostasis. Transcriptional profiling showed up-regulation of several peroxisome-localised antioxidant enzymes, most notably catalase. Analysis of antioxidant levels, catalase activity and catalase isoform 3 mutants (cat3) indicate that peroxisome-localised catalase plays a major role in restoring ROS homeostasis. Furthermore, protoplast cultures of pex11a, a peroxisome division mutant, and cat3 mutants show reduced induction of cell division. Taken together, the data indicate that peroxisome proliferation and catalase contribute to ROS homeostasis and subsequent protoplast division induction.